1993
DOI: 10.2166/wst.1993.0422
|View full text |Cite
|
Sign up to set email alerts
|

Use of Resource-Efficient Plants to Reduce Nitrogen, Phosphorus, and Pesticide Runoff in Residential and Commercial Landscapes

Abstract: Runoff from typical urban and suburban landscapes may contain significant levels of nitrogen, phosphorus, and a broad spectrum of various pesticides (mainly herbicides and insecticides) due to excessive application rates of these chemicals and high irrigation requirements of most commonly used landscape plant species. Preliminary water quality data (runoff) from a comparative study of 20 microwatersheds using 4 different levels of maintenance, show reductions in these types of pollutants in runoff for microwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Researchers have recommended the use of alternative plant materials in place of turfgrass in residential landscapes to conserve water resources and minimize environmental impacts (Hipp et al, 1993; Sacamano and Jones, 1975). The University of Florida–Institute of Food and Agricultural Sciences (UF‐IFAS) Florida‐Friendly Landscaping program promotes landscape best management practices to reduce the environmental impacts associated with urban landscape management.…”
mentioning
confidence: 99%
“…Researchers have recommended the use of alternative plant materials in place of turfgrass in residential landscapes to conserve water resources and minimize environmental impacts (Hipp et al, 1993; Sacamano and Jones, 1975). The University of Florida–Institute of Food and Agricultural Sciences (UF‐IFAS) Florida‐Friendly Landscaping program promotes landscape best management practices to reduce the environmental impacts associated with urban landscape management.…”
mentioning
confidence: 99%
“…Given environmental problems associated with loss of fertilizer nutrients from managed systems, there is great interest in research to evaluate residential landscape models for their potential to reduce N leaching. As a result, recent studies have demonstrated the potential for residential landscape models (i.e., vegetation type and associated maintenance regimes) to influence N leaching (Hipp et al, 1993; Broschat, 1995; Erickson et al, 2001; Bowman et al, 2002; Easton and Petrovic, 2004; Frank et al, 2005; Amador et al, 2007). Currently, the predominant residential landscape model in Florida consists of a monoculture of St. Augustinegrass [SA; Stenotaphrum secundatum (Walt.)…”
mentioning
confidence: 99%
“…The contribution of turf fertilization to total N nonpoint‐source losses appears to be relatively small on a river basin scale. Researchers have measured only small amounts of N in surface runoff from turf (Gross et al, 1990, 1991; Hipp et al, 1993). These results reflect the fact that most water generally moves through turf, rather than over turf, and that most applied N, unless in a slow release or organic form, is readily converted to NO 3 –N and moves through the soil profile rather than being lost through runoff.…”
mentioning
confidence: 99%